1995
DOI: 10.1111/j.1574-6976.1995.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin release proteins: mode of action, structure, and biotechnological application

Abstract: The mechanism by which Gram-negative bacteria like Escherichia coli secrete bacteriocins into the culture medium is unique and quite different from the mechanism by which other proteins are translocated across the two bacterial membranes, namely through the known branches of the general secretory pathway. The release of bacteriocins requires the expression and activity of a so-called bacteriocin release protein and the presence of the detergent-resistant phospholipase A in the outer membrane. The bacteriocin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 165 publications
(216 reference statements)
0
4
0
Order By: Relevance
“…Group A colicins require the activity of CRPs to reach the surrounding environment. Colicin release proteins of group A colicins are small, highly expressed lipoproteins (van der Wal et al ., ). They contain a signal peptide which accumulates in the bacterial inner membrane after cleavage from the mature, lipid‐modified CRP.…”
Section: Discussionmentioning
confidence: 97%
“…Group A colicins require the activity of CRPs to reach the surrounding environment. Colicin release proteins of group A colicins are small, highly expressed lipoproteins (van der Wal et al ., ). They contain a signal peptide which accumulates in the bacterial inner membrane after cleavage from the mature, lipid‐modified CRP.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our data do not rule out the possibility that the cells may not actively secrete the toxin across the outer membrane and instead, the bacteria may need to lyse to release the toxin. Cell lysis is required for the release of many colicins 3841 .…”
Section: Discussionmentioning
confidence: 99%
“…This lack of suppression could be due to the failure of the release of SyrM protein. It has been shown that the release of some colicins is regulated by colicin release protein (CRP)‐mediated cell lysis (Wal et al ., ; Cascales et al ., ) or during the course of phage lysis (Nedialkova et al ., ). As no SyrM‐associated lysis gene was identified in Pst , we thus speculate that this bacteriocin is released through an alternative mechanism which is still obscure at present.…”
Section: Discussionmentioning
confidence: 99%